Automated Lithographic Patterning Via Anodic Oxidation On Silicon Substrate - Jin, Gan Yeow (2010)
AFM is able to form localized oxide structures by applying a negative voltage through the tip, which acts like a \'pen\' to \'draw\' oxide lines on the substrate surface. This provides a simple and low cost technique to create nanoscale oxide patterns. However, the lack of control of the tip motion restricts this technique to only create simple patterns such as dots and straight lines. Since AFM was invented and primarily used for imaging purposes, typical AFM system does not allow user to customize the tip movements. It is fixed at a zig-zag raster scan path. There is also no synchronization between the tip voltage and movements to create automated complex patterns.